Perceived value and its influence on satisfaction and loyalty in a coastal city: a study from Lima, Peru. Issue 2 (4th May 2022) - Carvache-Franco, Mauricio; Alvarez-Risco, Aldo; Carvache-Franco, Orly; Carvache-Franco, Wilmer; Estrada-Merino, Alfredo; Villalobos-Alvarez, Diego
ABSTRACT: The objectives of this study are: (i) to identify the dimensions that make up the construct of perceived value in a coastal city; and (ii) to establish which dimensions of perceived value influence the satisfaction and loyalty variables of visitors to these destinations with coastal and marine characteristics. The study was carried out in the city of Lima, Peru, being a destination located in the coastal area of the Pacific Ocean. Three hundred and eighty-one questionnaires conducted on site were used. For data analysis, a factorial analysis and stepwise multiple regression method were performed. The results show two dimensions to perceived value, namely, economic-functional and emotional-social. The two dimensions that make up the perceived value are the predictors of tourist satisfaction and loyalty, with the economic-functional dimension being the most important predictor of satisfaction, whereas the emotional-social dimension is the important predictor in the loyalty towards coastal and marine destinations.